Inhibiting Factors Faced by Economics Education Students in Solving Reading Questions on TOEFL - Indrawati Pusparini; Ike Dian Puspita Sari; Anita Kurnia Rachman (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2025)
This research uses a qualitative descriptive research design with the aim of identifying what problems students face when completing Reading Section questions on the TOEFL. This research involved 30 Economics Education students who took TOEFL courses. Researchers used TOEFL questions taken from Longman's book to collect research data. Researchers conduct direct analysis of students' correct and incorrect answers on tests. After that, researchers conducted interviews with students who had wrong or correct answers to several questions to find out the cause of their difficulties. The research results found. The results of the analysis show that students have difficulty solving TOEFL questions in the reading section. Among other things, the problems faced by students are as follows: (1) students do not have sufficient English vocabulary, (2) students feel sleepy when reading long discourses, (3) students have difficulty finding the main idea in the text they read, and (4) students have difficulty finding the information conveyed in the texts they read.